FAKTOR-FAKTOR YANG MEMPENGARUHI TINDAK KECURANGAN DI PERUSAHAAN PERBANKAN - Kusumaningsih, Kadek Utami; Wirajaya, I Gde Ary (E-Jurnal Akuntansi; Vol 19 No 3 (2017), 2017)
This study aimed to analyze the factors that influence people do fraud in banking based on fraud triangle theory. Using  logistic regression analysis with 25 samples of Bank listed on IDX that choosen with purposive sampling method, the result shows that financial target which is proxied by ROE of the previous period, proportion of independent board of commissioners and the size of audit committee do not have an effect on fraud. Whereas personal financial need which is proxied by board ownership is proven to minimize the probability of bank fraud to occur.
Keywords: fraud, fraud triangle theory, bank